An Eye-Tracking Study on Text Comprehension While Listening to Music: Preliminary Results - Georgia Andreou; Maria Gkantaki (Applied Sciences)
The aim of the present study was to examine the effect of background music on text comprehension using eye-tracking technology. Ten Greek undergraduate students read four texts under the following four reading conditions: preferred music, non-preferred music, café noise, and in silence. Eye movements were tracked to assess visual patterns, while reading performance and attitudes were also evaluated. The results showed that fixation measures remained stable across conditions, suggesting that early visual processing is not significantly influenced by auditory distractions. However, reading performance significantly declined under non-preferred music, highlighting its disruptive impact on cognitive processing. Participants also reported greater difficulty and fatigue in this condition, consistent with an increased cognitive load. In contrast, preferred music and silence were associated with enhanced understanding, confidence, and immersion, café noise also had a moderate but manageable effect on reading outcomes. These findings underscore the importance of tailoring reading environments to individual preferences in order to optimize reading performance and engagement. Future research studies should focus on the effects of different musical attributes, such as tempo and genre, and use more complex reading tasks, in order to better understand how auditory stimuli interact with cognitive load and visual processing.